The development of Spiritual Nursing Care Theory using deductive axiomatic approach - Ashley A. Bangcola (Belitung Nursing Journal, 2021)
The concepts of spirituality and spiritual well-being are not novel ideas as they have been subjects of scrutiny in several studies. However, there has yet to be a formalized framework of spiritual nursing in the Philippines despite its importance. Developing such a framework is significant, especially since holistic nursing believes in the relationships among body, mind, and spirit. Thus, the Spiritual Nursing Care theory was conceptualized, which states that every person has holistic needs, including spiritual needs that must be satisfied to attain spiritual well-being. It forwards that for the patient’s spiritual needs to be met, what is required is the triumvirate interconnection among the nurse, the external environment, and the spiritual nursing care which may be provided by the nurse as a healthcare provider and the significant others or family as part of the external environment. The theory has two propositions that were subjected to validation studies that either strengthened or repudiated the propositions presented: (1) the meaning of spirituality differs from person to person, and (2) the patient’s spiritual well-being is influenced by the nurse’s spiritual care competence, as well as the patient’s internal and external variables.